As fases pictóricas de Wega Nery - Rosin, Priscila (2011)
Wega Nery (1912-2007) was a Brazilian artist with 60 years of artistic career and cataloged over 1000 works. In this long history, there were artistic works from different phases, which were: Academic Influences ; Formal Studies ; Drawing ; Stained Glass ; Transition and Expansion ; Imaginary Landscapes ; Mitigation . Wega began her career in 1946 with figurative works, fruits of her period of study at the School of Fine Arts, theses works brought nostalgic themes of childhood, showing the home and family environment of the artist. After designing her painting and pictorial representation and deepen the studies of painting, Wega entered in black and white world of non-referrals and non-realities, it was the phase of the ink monochrome drawings. As your freedom to represent the actual increased, the color reappeared, now in abstraction with small-format screens, even geometric drawing and palette contained, informally known as "Stained Glass". In the 60‟s and 70‟s, the gestural painting has become a tool of expression in the creation of the artist, who worked with generous flicks forming large patches of vibrant colors, made with a spatula that followed her emotional impulse, it was the phase "Imaginary Landscapes". In the mid-80‟s, due to advanced age, the artist has slowed her production, which set the phase Mitigation . During this entire period devoted to art, Wega developed her artistic language and won national and international recognition. The "Portraits" were also important works that have appeared in most Wega pictorial phases